Upsetting Constructions of Safety: An Auto-Ethnography of a Suburb - Chapados, Sydney (Contingent Horizons: The York University Student Journal of Anthropology, 2022)
This article examines how certain neighbourhoods and the populations that reside in them might be understood as safe and good by presenting observations from a walking, autoethnography through and around the suburb in which the author resides. The messages that societies receive and internalize about people who experience poverty are primarily constructed out of neoliberal institutions that uphold the idea that those who live in poverty are there by choice or incapacity and face the appropriate consequences of that choice. Neoliberal discourses devalue the lives of those experiencing poverty by suggesting that they are morally, physically, or mentally incapable of being responsible for themselves. While anyone could potentially experience poverty, the relational construct of the upper class/lower class creates a metaphorical divide that requires deep rethinking to transcend. When spaces are demarcated as unsafe or violent, other spaces are relationally marked as safe or secure. The article concludes that controlling outward appearances largely creates and reinforces constructions of suburban areas as safe in relation to the construction of other areas as unsafe and violent. However, the intensive focus on controlling appearances leads to a mistrust of others and the sacrificing of communities that once existed and thrived.